A Scoping Review of Interventions for Family Bereavement Care during the COVID-19 Pandemic - Carlos Laranjeira; Débora Moura; Maria Aparecida Salci; Lígia Carreira; Eduardo Covre; André Jaques; Roberto Nakamura Cuman; Sonia Marcon; Ana Querido (Behavioral Sciences, 2022)
The death of a loved one is a major stressor, and bereaved people are at a higher risk of negative health effects. This risk is higher during the COVID-19 pandemic, which raises the need for understanding existing bereavement support interventions. This scoping review aimed to map and summarize findings from the existing literature regarding bereavement support interventions (i.e., psychosocial and psychotherapeutic interventions) for family carers of people who died of COVID-19. The Arksey and O’Malley methodological framework was used. Five databases—Medline, PubMed, CINAHL, Scopus, and Web of Science—were searched for articles available from the inception of COVID-19 pandemic (March 2020) to January 2022, following the PRISMA guidelines. Among the 990 studies identified, only seven met this study’s inclusion criteria. The analysis comprised three key topics: types of support programmes and bereavement interventions; tools used to measure the outcomes; and evidence of the impacts of the interventions. All studies analysed included interdisciplinary interventions, commonly developed in clinical settings. Support for recently bereaved individuals can entail cognitive behavioural therapy strategies and other tools to educate, guide, support, and promote healthy integration of loss. To mitigate the effects of non-normative family bereavement, we recommend a systematic approach and coordination between organizational settings, including access to informal and professional support, in order to find hope while navigating the aftermath of COVID-19.